Academic Service Quality Analysis Techniques for Student Satisfaction - Eko Ngabdul Shodikin; Nur Saidah; Setia Murningsih (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Data analysis techniques have been continuously evolving over the years with various innovations emerging in relation to the techniques used by researchers in their studies. This study aims to analyze the methods used to analyze service quality in relation to student satisfaction. The study is a qualitative descriptive study that uses traditional review analysis techniques. Based on the results of the traditional review, it can be seen that not all journals provide complete information. Research on service quality and student satisfaction has been conducted in several countries such as Indonesia, Malaysia, South Korea, and Bangladesh. Sampling techniques for each study vary depending on field conditions and limitations of manpower, time, and cost. The sampling technique aims to facilitate researchers in obtaining data from respondents. Quantitative research has independent and dependent variables but can also be supplemented with moderating or intervening variables. Each variable can be measured directly or indirectly. Variables that cannot be measured directly require indicators to describe the variable. There are also variables that consist of several dimensions, with each dimension having several indicators. The analysis techniques used to test the relationship between service quality and student satisfaction in this study include multiple linear regression, path analysis, confirmatory factor analysis, and structural equation modeling. This proves that the development of science leads to a diversity of methods that can be used to test a hypothesis.